(untitled) (Nigerian Journal of Physiological Sciences, 2025)
This study investigates the relationship between bone-related markers and dyslipidemia in postmenopausal women in Owo metropolitan, recognizing the critical role of lipids in physiological functions and the heightened risk of cardiovascular diseases with menopause-induced lipid metabolism changes. A total of 100 subjects were enrolled, including 60 postmenopausal (PMP) women, 20 premenopausal (PRM) women, and 20 reproductive women aged (RWA). Fasting blood samples were collected and analyzed for various parameters using standard laboratory procedures. Statistical analysis revealed significantly elevated levels of Total Cholesterol (TC), HDL-C, and LDL-C in both PMP and PRM subjects compared to the RWA (p<0.05). In contrast, ALP, inorganic phosphate, and uric acid levels were significantly higher in PMP and PRM subjects, while FBS, calcium, and vitamin D levels were lower (p<0.05). Furthermore, inorganic phosphate had a strong positive association with TC, TG, and LDL-C among PMP women. These data emphasize the considerable difference in lipid profiles between premenopausal and postmenopausal women, as well as the higher prevalence of dyslipidemia after menopause.